Cellular Markers of Active Disease and Cure in Different Forms of Leishmania infantum-Induced Disease - Botana, Laura; Matía, Belén; San Martin, Juan V.; Romero-Maté, Alberto; Castro, Alicia; Molina, Laura; Fernandez, Laura; Ibarra-Meneses, Ana; Aguado, Marta; Sánchez, Carmen; Horrillo, Luis; Chicharro, Carmen; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Increased numbers of peripheral blood mononucleocytes (PBMC) and increased IFN-γ secretion following in vitro challenge of blood samples with soluble Leishmania antigen (SLA), have been proposed as biomarkers of specific cell-mediated immunity, indicating that treatment of visceral leishmaniasis (VL) has been successful. However, Leishmania infantum infection may manifest as cutaneous leishmaniasis (CL), and less commonly as localized leishmanial lymphadenopathy (LLL) or mucosal leishmaniasis (ML). The present work examines the value of these biomarkers as indicators of cured leishmaniasis presenting in these different forms. Blood samples were collected before and after treatment from patients living in Fuenlabrada (Madrid, Spain), an L. infantum-endemic area recently the center of a leishmaniasis outbreak. All samples were subjected to Leishmania-specific PCR, serological tests (IFAT and rK39-ICT), and the SLA-cell proliferation assay (SLA-CPA), recording PBMC proliferation and the associated changes in IFN-γ production. Differences in the results recorded for the active and cured conditions were only significant for VL. PCR returned positive results in 67% of patients with active VL and in 3% of those with cured leishmaniasis. Similarly, rK39-ICT returned a positive result in 77% of active VL samples vs. 52% in cured VL samples, and IFAT in 90% vs. 56%; in the SLA-CPA, PBMC proliferation was seen in 16% vs. 90%, and an associated increase in IFN-γ production of 14 and 84%, respectively. The present findings reinforce the idea that PBMC proliferation and increased IFN-γ production in SLA-stimulated PBMC provide biomarkers of clinical cure in VL. Other tests are urgently needed to distinguish between the cured and active forms of the other types of clinical leishmaniasis caused by L. infantum.